2018
DOI: 10.1002/celc.201800016
|View full text |Cite
|
Sign up to set email alerts
|

Tin‐Assisted Sb2S3 Nanoparticles Uniformly Grafted on Graphene Effectively Improves Sodium‐Ion Storage Performance

Abstract: Herein, composites of tin‐assisted antimony sulfide decorated on reduced graphene oxide (Sn@Sb2S3‐rGO) were prepared by using a simple hydrothermal method. As an anode material of sodium‐ion batteries, the Sn@Sb2S3‐rGO composites exhibited good electrochemical performance with an initial discharge (sodiation) specific capacity of 1002.0 mAh g−1, and they maintained a specific capacity of approximately 600 mAh g−1 at a current density of 200 mA g−1 after 60 cycles. The good performances could be explained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…[ 164,165 ] The first intercept at Z ’ axis (at very high frequency region) corresponds to the electrolyte resistance ( R S ), the former semicircle position at high frequency region is assigned to interlayer diffusion process on the stable SEI nanolayer ( R Suf ), the latter semicircle at medium frequency region is attributed to R CT , and the final slope tail at low frequency region is ascribed to the Warburg impedance ( Z W ) corresponding to the ion diffusion impedance into porous structure. [ 166 ] Hence, the R mainly reflects the intrinsic property of the electrode, and the fitting linear was further carried out to evaluate the Warburg coefficient (σ) and D Na+ according to the Equations (5) and (6) ZW=σω1/2jσω1/2 σ=RTn2F2s2 1C00D0+1CR0D0 σω −1/2 corresponds to real part ( Z ′), −j σω −1/2 belongs to imaginary part ( Z ″) and Z W is Warburg impedance. Where R is the gas constant (8.314 J mol −1 K −1 ), T is Kelvin temperature (293.15 K), S is the area of electrodes (cm 2 ), n is the electronic transfer number, F is the Faradic constant (96 485, C mol −1 ), and C is the concentration of Na ions in the lattice (mol L −1 ).…”
Section: Kinetics/thermodynamic Reaction Explorationmentioning
confidence: 99%
“…[ 164,165 ] The first intercept at Z ’ axis (at very high frequency region) corresponds to the electrolyte resistance ( R S ), the former semicircle position at high frequency region is assigned to interlayer diffusion process on the stable SEI nanolayer ( R Suf ), the latter semicircle at medium frequency region is attributed to R CT , and the final slope tail at low frequency region is ascribed to the Warburg impedance ( Z W ) corresponding to the ion diffusion impedance into porous structure. [ 166 ] Hence, the R mainly reflects the intrinsic property of the electrode, and the fitting linear was further carried out to evaluate the Warburg coefficient (σ) and D Na+ according to the Equations (5) and (6) ZW=σω1/2jσω1/2 σ=RTn2F2s2 1C00D0+1CR0D0 σω −1/2 corresponds to real part ( Z ′), −j σω −1/2 belongs to imaginary part ( Z ″) and Z W is Warburg impedance. Where R is the gas constant (8.314 J mol −1 K −1 ), T is Kelvin temperature (293.15 K), S is the area of electrodes (cm 2 ), n is the electronic transfer number, F is the Faradic constant (96 485, C mol −1 ), and C is the concentration of Na ions in the lattice (mol L −1 ).…”
Section: Kinetics/thermodynamic Reaction Explorationmentioning
confidence: 99%
“…Nowadays, introducing various elements into the Sb 2 S 3 is quite common because of structural stability and stable cycleability . For example, Deng et al reported that the prepared Sn@Sb 2 S 3 –RGO composite exhibited a good electrochemical performance with an initial discharge specific capacity of 1002 mAh g −1 , and they maintained 600 mAh g −1 at a current density of 200 mA g −1 after 60 cycles . The SnS 2 /Sb 2 S 3 @RGO heterostructure has been prepared by Wang et al and reported a high reversible capacity of 642 mAh g −1 at a current density of 0.2 A g −1 and good cyclic stability without capacity loss in 100 cycles …”
Section: Carbon Supported Antimony Composite For Sibsmentioning
confidence: 99%
“…To solve these problems, homogeneous-width Sb 2 S 3 nanorods (Sb 2 S 3 NRs) and graphene oxide (GO) were used to make Sb 2 S 3 NRs@rGO anchored on reduced graphene oxide (rGO) [13][14][15][16]. Uniform sized Sb 2 S 3 NRs could compensate volume variation to some degrees while intercalation of Na+ than various sized nanorods [17][18][19]. Reduced graphene oxide (rGO) layers not only have enough interstitial spots to receive Na + but also have substantial conductivity making electron transfer easily.…”
Section: Introductionmentioning
confidence: 99%